Impact of home versus clinic-based management of chronic heart failure: The WHICH? (Which heart failure intervention is most cost-effective & consumer friendly in reducing hospital care) multicenter, randomized trial - Stewart, S.; Carrington, M.; Marwick, T.; Davidson, P.; MacDonald, P.; Horowitz, J.; Krum, H.; Newton, P.; Reid, Christopher; Chan, Y.; Scuffham, P. (2012)
Objectives: The goal of this study was to make a head-to-head comparison of 2 common forms of multidisciplinary chronic heart failure (CHF) management. Background: Although direct patient contact appears to be best in delivering CHF management overall, the precise form to optimize health outcomes is less clear. Methods: This prospective, multicenter randomized controlled trial with blinded endpoint adjudication comprised 280 hospitalized CHF patients (73% male, age 71 ± 14 years, and 73% with left ventricular ejection fraction =45%) randomized to home-based intervention (HBI) or specialized CHF clinic-based intervention (CBI). The primary endpoint was all-cause, unplanned hospitalization or death during 12- to 18-month follow-up. Secondary endpoints included type/duration of hospitalization and healthcare costs. Results: The primary endpoint occurred in 102 of 143 (71%) HBI versus 104 of 137 (76%) CBI patients (adjusted hazard ratio [HR]: 0.97 [95% confidence interval (CI): 0.73 to 1.30], p = 0.861): 96 (67.1%) HBI versus 95 (69.3%) CBI patients had an unplanned hospitalization (p = 0.887), and 31 (21.7%) versus 38 (27.7%) died (p = 0.252). The median duration of each unplanned hospitalization was significantly less in the HBI group (4.0 [interquartile range (IQR): 2.0 to 7.0] days vs. 6.0 [IQR: 3.5 to 13] days; p = 0.004). Overall, 75% of all hospitalization was attributable to 64 (22.9%) patients, of whom 43 (67%) were CBI patients (adjusted odds ratio: 2.55 [95% CI: 1.37 to 4.73], p = 0.003). HBI was associated with significantly fewer days of all-cause hospitalization (-35%; p = 0.003) and from cardiovascular causes (-37%; p = 0.025) but not for CHF (-24%; p = 0.218). Consequently, healthcare costs ($AU3.93 vs. $AU5.53 million) were significantly less for the HBI group (median: $AU34 [IQR: 13 to 81] per day vs. $AU52 [17 to 140] per day; p = 0.030). Conclusions: HBI was not superior to CBI in reducing all-cause death or hospitalization. However, HBI was associated with significantly lower healthcare costs, attributable to fewer days of hospitalization. (Which Heart failure Intervention is most Cost-effective & consumer friendly in reducing Hospital care [WHICH?]; ACTRN12607000069459) © 2012 American College of Cardiology Foundation.